Sealant and composite bond strength to enamel with antibacterial/self-etching adhesives - N. EMINKAHYAGIL, S. GOKALP, Y. KORKMAZ, M. BASEREN, & E. KARABULUT (Paediatric Dentistry, 2005)
The enamel in pits and fissures undergoing preventive or ultraconservative resin restorations may be affected by secondary caries.